2017
DOI: 10.1111/hsc.12530
|View full text |Cite
|
Sign up to set email alerts
|

Perceived needs of carers of people with psychosis: An Australian longitudinal population-based study of caregivers of people with psychotic disorders

Abstract: Studies have documented the perceived needs of carers of people with psychosis but most recruitment has utilised convenience sampling resulting in limited understanding of carers' needs. This longitudinal study was conducted within the second Australian prevalence study of psychosis, aiming to obtain generalisable findings regarding perceived needs of carers of people with psychosis. Semi-structured interviews were conducted with 98 carers of people with psychosis recruited in the Australian prevalence study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(61 reference statements)
2
14
0
1
Order By: Relevance
“…smaller scale and qualitative studies of carers, which have identified a similar range of unmet needs for information and support (Lawn and McMahon, 2015;Poon et al, 2018). For example, Poon et al (2018) found that carers of people with psychotic disorders also reported needs for financial support, respite care and emotional support, consistent with the main unmet needs identified by mental health carers in the 2012 SDAC.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…smaller scale and qualitative studies of carers, which have identified a similar range of unmet needs for information and support (Lawn and McMahon, 2015;Poon et al, 2018). For example, Poon et al (2018) found that carers of people with psychotic disorders also reported needs for financial support, respite care and emotional support, consistent with the main unmet needs identified by mental health carers in the 2012 SDAC.…”
mentioning
confidence: 87%
“…smaller scale and qualitative studies of carers, which have identified a similar range of unmet needs for information and support (Lawn and McMahon, 2015;Poon et al, 2018). For example, Poon et al (2018) found that carers of people with psychotic disorders also reported needs for financial support, respite care and emotional support, consistent with the main unmet needs identified by mental health carers in the 2012 SDAC. While previous studies have highlighted the importance of emotional support tasks for mental health carers (Pirkis et al, 2010;Carers Victoria, 2013), to our knowledge, this is the first study to quantify differences in caring tasks for mental health v. other disability carers; specifically that more mental health carers provide emotional support but fewer assist with practical tasks and ADLs.…”
mentioning
confidence: 87%
“…On one hand, caregivers express concern that divulging information poses risks to relationships and may diminish trust. On the other hand, professionals describe a lack of confidence in sharing information with caregivers (Poon, Joubert, & Harvey, ; Rapaport, Bellringer, Pinfold, & Huxley, ). This is despite the availability of a range of published guidance for both professionals and caregivers about ways to manage information without compromising regulations about confidentiality (Slade et al, ; Rethink Mental Illness, no date; Royal College of Psychiatrists, no date), suggesting incomplete implementation of guidelines into practice and may indicate a training need for both professionals and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…There may therefore, be value in research designed to explore tailored family‐based interventions at times of service transition. Attention must however be paid to effective implementation of any such intervention to avoid the implementation gaps in family based interventions reported internationally for some time (Poon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…La adaptación del programa a las características de los cuidadores de pacientes con esquizofrenia fue posible gracias a la similitud de necesidades entre ambas poblaciones. Tanto los cuidadores de enfermos con demencia como con trastorno mental grave manifiestan similares necesidades de información, apoyo emocional, manejo del paciente y autocuidados (Poon, Joubert y Harvey, 2017;Sachs, 2006;Whitlatch y Orsulic-Jeras, 2018). Para ello, se modificó el lenguaje y los contenidos de las sesiones (los ejercicios prácticos y los materiales didácticos).…”
Section: Intervenciónunclassified